Developing Business and Technology Strategy - Hämäläinen, Hannu (My University, 2011)
The purpose of this thesis was to develop a business strategy and an aligned technology strategy for a multinational company. The aim was to find suitable methods, techniques and models to create a coherent and clear strategy aligned to corporate strategic objectives. The thesis work was limited to depicting what was done, how it was done, and why, instead of giving universal solutions to build strategies or depicting outcomes. The framework of the thesis was limited to a generic theoretical part, describing definitions, evolution of strategic thinking as well as tools and models for strategic analysis. The experimental part was centered on a process created for one company case utilizing tools and models which were selected based on learnings from literature and the framework and context of the company. From scientific point of view, the work is more of a descriptive and constructive nature, based on only one case, thus endeavors to generalize conclusions have to be taken by caution. Key learnings were that strategy can be seen differently depending on how it is defined. Secondly, it was seen that means will affect ends and vice versa, thus selection of the strategy process is important as it affects outcomes.
Keywords: Technology; strategy; management; business; fi=Tuotantotalous|en=Industrial Management|